PERBEDAAN ANTROPOMETRI BAYI BARU LAHIR ANTARA IBU HAMIL YANG MELAKUKAN PRENATAL YOGA DAN SENAM HAMIL - Imelda Fitri; Della Ardina; Sara Herlina (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2025)
The incidence of anxiety among pregnant women in Indonesia reaches 28.7%, with moderate anxiety occurring in pregnant women nearing childbirth. Excessive maternal anxiety increases stress hormone levels, affecting the fetus, such as increasing the risk of preterm birth and low birth weight. Objective: To determine the differences in anthropometry (weight, length, and head circumference) of newborns between pregnant women practicing prenatal yoga and those participating in pregnancy exercises in Sungai Asam Village, Reteh District. Method: This study uses a quasi-experimental method with a two-group posttest design. The study was conducted in May-June 2024 in Sungai Asam Village, Reteh District. The research instruments included prenatal yoga checklist sheets, pregnancy exercise guides, and delivery reports. The sampling technique used was purposive sampling with 28 samples (14 for prenatal yoga intervention and 14 for pregnancy exercise intervention). Data analysis techniques included univariate and bivariate analysis using Independent T-test and Mann-Whitney test in SPSS 25. Results: The study showed no differences in anthropometry (weight, length, and head circumference) of newborns between pregnant women practicing prenatal yoga and those participating in pregnancy exercises. The weight of newborns had a p-value of 0.113, body length had a p-value of 0.464, and head circumference had a p-value of 0.978. Conclusion: Prenatal exercise (prenatal yoga and pregnancy exercises) is beneficial in optimizing fetal growth and development, as indicated by the newborns’ anthropometric measurements (weight, length, head circumference) within normal limits.